Intention to adopt e-Business amongst small medium enterprises: a case study in Terengganu / Nurmuslimah Kamilah Abdullah and Azyanee Luqman - Abdullah, Nurmuslimah Kamilah; Luqman, Azyanee (2010)
This research focuses on Terengganu Small Medium Enterprises (SMEs) established in Terengganu developed districts which are Kuala Terengganu and Kemaman. The aims of this study are to identify the relationship between relative advantage, compatibility, complexity, trialability and observability with e-business adoption and to identify the e-business adoption level among SMEs in Kemaman and Kuala Terengganu. A questionnaire was the instrument used in getting the data with ninety samples from Kuala Terengganu and sixty-four samples from Kemaman. The Innovation Diffusion Theory (IDT) was adapted based on the five factors identified by Rogers (2003) which are relative advantage, compatibility, complexity, trialability and observability that affect the level of e-business adoption. For this exploratory study, all identified independent variables had relationships with e-business adoption but with less than moderate level of association. Five adoption levels were identified namely innovator, early adopter, early majority, late majority and laggard. Respondents in Kemaman dominated the innovator, early adopter and late majority categories whereas respondents in Kuala Terengganu dominated the early majority and laggard categories.